Lipopolysaccharides trigger synthesis of the allelochemical sorgoleone in cell cultures of Sorghum bicolor. (2nd October 2020) - Mareya, Charity R; Tugizimana, Fidele; Steenkamp, Paul; Piater, Lizelle; Dubery, Ian A
ABSTRACT: The use of plant cell suspension culture systems has demonstrated to be highly suitable for metabolomics investigations of inducible defense responses. Here we report on sorghum cell suspension cultures that were elicited with purified lipopolysaccharides from the sorghum pathogen Burkholderia andropogonis, to activate metabolic pathways involved in the chemical defenses of the plant. Metabolomic analysis using liquid chromatography coupled to mass spectrometry identified a resorcinol phenolic lipid, annotated as sorgoleone, as one of the biomarkers associated with the LPS-induced response. Sorgoleone is a semiochemical and an allelochemical, synthesized by specialized root hair cells and the major component of the hydrophobic root exudate of sorghum. Its detection in undifferentiated cells might indicate a previously undescribed role for this phytochemical in plant defense responses.